Persistence with dual antiplatelet therapy after percutaneous coronary intervention for ST-segment elevation acute coronary syndrome: a population-based cohort study in Catalonia (Spain). Issue 7 (23rd July 2019) - Ribera, Aida; Ferreira-Gonzalez, Ignacio; Marsal, Josep Ramon; Oristrell, Gerard; Faixedas, Maria Teresa; Rosas, Alba; Tizón-Marcos, Helena; Rojas, Sergio; Labata, Carlos; Cardenas, Merida; Homs, Silvia; Tomas-Querol, Carlos; et al.
Abstract : Objectives: Guidelines recommending 12-month dual antiplatelet therapy (DAPT) in patients with ST-elevation acute coronary syndrome (STEACS) undergoing percutaneous coronary intervention (PCI) were published in year 2012. We aimed to describe the influence of guideline implementation on the trend in 12-month persistence with DAPT between 2010 and 2015 and to evaluate its relationship with DAPT duration regimens recommended at discharge from PCI hospitals. Design: Observational study based on region-wide registry data linked to pharmacy billing data for DAPT follow-up. Setting: All PCI hospitals (10) belonging to the acute myocardial infarction (AMI) code network in Catalonia (Spain). Participants: 10 711 STEACS patients undergoing PCI between 2010 and 2015 were followed up. Primary and secondary outcome measures: Primary outcome was 12-month persistence with DAPT. Calendar year quarter, publication of guidelines, DAPT duration regimen recommended in the hospital discharge report, baseline patient characteristics and significant interactions were included in mixed-effects logistic regression based interrupted time-series models. Results: The proportion of patients on-DAPT at 12 months increased from 58% (56–60) in 2010 to 73% (71–75) in 2015. The rate of 12-month persistence with DAPT significantly increased after the publication of clinical guidelines with a time lag of 1 year (OR=1.20; 95% CI 1.11 to 1.30). A higher risk profile, more extensive and complex coronary disease, use of drug-eluting stents (OR=1.90; 95% CI 1.50 to 2.40) and a 12-month DAPT regimen recommendation at discharge from the PCI hospital (OR=5.76; 95% CI 3.26 to 10.2) were associated with 12-month persistence. Conclusion: Persistence with 12-month DAPT has increased since publication of clinical guidelines. Even though most patients were discharged on DAPT, only 73% with potential indication were on-DAPT 12 months after PCI. A guideline-based recommendation at PCI hospital discharge was highly associated with full persistence with DAPT. Establishing evidence-based, common prescribing criteria across hospitals in the AMI-network would favour adherence and reduce variability.